PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (Studi Kasus pada Perawat Rumah Sakit Islam Sakinah Mojokerto) - Robiah, Rifka Anisatur (Jurnal Ilmiah Mahasiswa FEB, 2017)
The research is administered at Sakinah Islamic Hospital Mojokerto, aiming to analyze the influence of the organizational culture and organizational commitment on organizational citizenship behavior of the nurses. This explanatory research explains the causal relation among the variables through hypothesis testing. The research samples are all regular nurses in Sakinah Islamic Hospital Mojokerto, consisting of 129 people in total. The data are collected through questionnaires measured by Likert’s scale and analyzed descriptively using multiple linear regression method, by F test, t test, and dominant test. The results of the analysis show that the organizational culture (X1) and organizational commitment (X2) have simultaneous effect on organizational citizenship behaviour (Y). The results of T test confirm that the organizational culture (X1) has positive and significant effects on organizational citizenship behavior ( (Y). The results of T test also illustrate that organizational commitment (X2) has significant effects on organizational citizenship behavior (Y). Finally, the results also show that organizational commitment (X2) has the most dominant effect on the organizational citizenship behavior (OCB) of the nurses in Sakinah Islamic Hospital Mojokerto.Keywords: Work Environment, Work Stress, Morale of Employees.